2016
DOI: 10.1111/ijlh.12553
|View full text |Cite
|
Sign up to set email alerts
|

Variability in platelet dense granule adenosine triphosphate release findings amongst patients tested multiple times as part of an assessment for a bleeding disorder

Abstract: The variability in platelet dense granule ATP release findings amongst patients assessed for diagnostic purposes suggests that the test has limited value for diagnosing platelet disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 21 publications
(38 reference statements)
2
52
0
Order By: Relevance
“…We found DGD in 6.5% of patient samples tested between 2006 and 2017 (excluding samples collected for NASCOLA EQA) and, not surprising, in a higher proportion (34%) of individuals that were recruited to a research study that had confirmed DGD as an inclusion criterion. Like our recent studies, we observed that the majority of patients referred for PFD testing were female, likely due to their increased burden of hemostatic challenges from menstruation and childbirth. Importantly, confirmed DGD by whole mount EM was associated with increased bleeding symptoms and a higher likelihood of having a bleeding disorder, which provides important evidence on clinical associations for reduced DG counts.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…We found DGD in 6.5% of patient samples tested between 2006 and 2017 (excluding samples collected for NASCOLA EQA) and, not surprising, in a higher proportion (34%) of individuals that were recruited to a research study that had confirmed DGD as an inclusion criterion. Like our recent studies, we observed that the majority of patients referred for PFD testing were female, likely due to their increased burden of hemostatic challenges from menstruation and childbirth. Importantly, confirmed DGD by whole mount EM was associated with increased bleeding symptoms and a higher likelihood of having a bleeding disorder, which provides important evidence on clinical associations for reduced DG counts.…”
Section: Discussionsupporting
confidence: 78%
“…Our estimates of the respective sensitivities of LTA and DG ATP release (estimated by lumi‐aggregometry), for detecting abnormalities due to DGD, were only ~52% and 70%, which is inadequate to screen for DGD. Although impaired DG ATP release with multiple agonists was present in some participants with DGD, the assessment of DG ATP release has questionable diagnostic usefulness as the findings show considerable variability, and even if ATP release is consistently impaired, the finding does not show a significant relationship to elevated bleeding scores or the clinical diagnosis of a bleeding disorder . Laboratories should be cautious when interpreting data for DG ATP release as we noted that only 30% of individuals with confirmed DGD had impaired ATP release with all agonists.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…For LTA, MA findings provide important quantitative information for the test interpretation and the pattern of abnormalities can be readily interpreted using the North American guidelines . With both LTA and release assays, single agonist abnormalities are usually a false positive and are much less predictive of a bleeding disorder than multiple agonist abnormalities . Some laboratories perform LTA on automated coagulation analyzers, which appears to provide comparable findings to traditional LTA .…”
Section: Resultsmentioning
confidence: 99%